The Correlation Between Religiosity and Free Sexual Behavior in Early Adults in Sukajadi Sub District, Pekanbaru - Asmida, Asmida; Armayeti, Leni; Binqalbi Ruzain, Raihantu (Journal of Islamic and Contemporary Psychology, 2023)
This research aims to study the Correlation between religiosity and free-sex behaviour in adulthood early in Sukajadi District. One hundred people were selected as samples using the purposive sampling technique. The measuring instrument used was a religiosity scale of 27 items and a scale of free sex behaviour of 30 items. Pearson product-moment correlation analysis was used to analyze the data in this study. The statistical analysis results showed a significant negative Correlation between religiosity and free-sex behaviour, with a correlation value of r = 0.387 and a significance value of sig = 0.000 (p <0.05). This means that the higher the level of one's religiosity, the lower the free-sex behaviour in early adulthood. Conversely, the lower the level of one's religiosity, the higher the free-sex behaviour in early adulthood. The practical contribution of religiosity to free-sex behaviour is 15%.